2021
DOI: 10.14701/ahbps.2021.25.2.230
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diabetes mellitus on morbidity and survival after pancreaticoduodenectomy for malignancy

Abstract: Backgrounds/Aims: Diabetes mellitus (DM) is a known risk factor for morbidity, length of hospital stay, or mortality after surgery, however, its impact on postoperative course and long-term survival after pancreaticoduodenectomy (PD) is not clear. Methods: This is a retrospective analysis of prospectively maintained database of 141 patients with periampullary and pancreatic head adenocarcinoma operated between January 2001 and March 2019. Clinico-pathological records and follow-up data were retrieved and analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…23 The impact of diabetes on survival outcomes in pancreatic cancer patients treated with resection is still unclear, with some studies proposing no statistically significant differences in pancreatic fistula, delayed gastric emptying, infection, and perioperative death between diabetic and nondiabetic groups. 24 However, a recent study that included 19,054 post-PD patients found that metabolic syndrome, represented by diabetes mellitus, increased the incidence of postoperative complications (such as pulmonary embolism, acute renal failure, cardiac arrest, and delayed gastric emptying) after PD (p < 0.05). 25 As another potential risk factor, smoking is not only a direct contributor to lung cancer, but also increases the incidence of postoperative anastomotic margin ulceration and even structural disruption of the anastomosis after pancreaticoduodenal surgery, which can lead to pancreatic fistula and bleeding.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…23 The impact of diabetes on survival outcomes in pancreatic cancer patients treated with resection is still unclear, with some studies proposing no statistically significant differences in pancreatic fistula, delayed gastric emptying, infection, and perioperative death between diabetic and nondiabetic groups. 24 However, a recent study that included 19,054 post-PD patients found that metabolic syndrome, represented by diabetes mellitus, increased the incidence of postoperative complications (such as pulmonary embolism, acute renal failure, cardiac arrest, and delayed gastric emptying) after PD (p < 0.05). 25 As another potential risk factor, smoking is not only a direct contributor to lung cancer, but also increases the incidence of postoperative anastomotic margin ulceration and even structural disruption of the anastomosis after pancreaticoduodenal surgery, which can lead to pancreatic fistula and bleeding.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, pancreatic cancer patients with concurrent diabetes are at increased risk of tumor invasion into surrounding tissues and nerves. 24 Nomograms are graphically illustrated statistical prediction models that predict patient-specific risks for given outcomes. The first nomogram model was established by Memorial Sloan-Kettering Cancer Center (MSKCC) in 2004.…”
Section: Discussionmentioning
confidence: 99%
“…Deo et al [ 29 ] have found that preoperative DM does not affect surgical outcomes, although five-year survival is lower among diabetics. Since patients with diabetics are thought to have a soft pancreas with a high fat content (both risk factors for POPF) [ 29 ], it has been suggested they have a higher risk of developing POPF. However, two recent meta-analyses have disputed this [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This theory was partly confirmed by a multivariable analysis in which recent T2DM onset had an independent association with PDAC relapse (HR = 1.45, 95% CI [1.06–1.99]) ( Balzano et al, 2016 ). In addition, the negative impact of DM on 3- and 5-year disease-free survival was demonstrated with no marked effect on the postsurgical course in patients with pancreatic and periampullary adenocarcinoma ( Deo et al, 2021 ), implying that the processes determining the impact of T2DM might be delayed. Long-standing T2DM is associated with a shorter PFS, while in the early T2DM group, both PFS and OS differ from patient to patient ( Bitterman et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with T2DM and PC also have a poor response to chemotherapy, larger tumors, and an elevated risk of death post-chemotherapy ( Ma et al, 2019 ). Nevertheless, some studies failed to observe the significant effects of preoperative T2DM on the postoperative course ( Deo et al, 2021 ) and prognosis ( Balzano et al, 2016 ). A meta-analysis of 29 trials with 33 risk estimates suggested that T2DM is associated with reduced survival only in patients with resectable PC ( Mao et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%